Legal Issues Regarding the Role of the Police in Carrying Out Investigations into Human Trafficking Crimes - Zaqi Ur Rachman; Gunarto Gunarto (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The interrelationship between investigators and relevant agencies responsible for protecting victims of human trafficking has also not been optimized. Another problem, which often presents an obstacle, is a lack of understanding of the legal substance of the criminal provisions of the Law on the Eradication of Human Trafficking, which results in delays in case resolution and/or disagreements between investigators and prosecutors regarding the interpretation and analysis of criminal cases under investigation. The aim of this research is to determine and analyze (1) the systematic development of human trafficking in Indonesia, (2) the police's investigative methods for human trafficking crimes, and (3) the legal problems of police investigations into human trafficking crimes. The approach method used in this research is normative juridical. The specifications of this research are analytical descriptive. The data source used is secondary data. Secondary data is data obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. The research results and discussion can be concluded: (1) In the case of human trafficking in Indonesia, which has been a hot topic in the news for the past few years, the practice has increased, with several ASEAN countries, namely Myanmar, Thailand, Cambodia, Vietnam, and Laos, as the destination for exploitation. The highest number of human trafficking cases is Cambodia. (2) Mechanistically, the first step taken is an investigation and inquiry into reports of suspected human trafficking. Investigators use modern investigative techniques to uncover human trafficking networks that frequently change locations to avoid detection by law enforcement. The process of investigating human trafficking cases begins with receiving reports from the public or findings in the field. In this process, investigators have the authority to receive reports/complaints, both in writing, verbally, and electronically, regarding suspected human trafficking. (3) The problems that arise in the police's efforts to investigate human trafficking crimes are primarily due to the characteristics of this crime, which is carried out through a disconnected network pattern. This makes it difficult to handle or prevent human trafficking. The disconnected network starts from recruitment, transportation, and shelter.